64.1k views
4 votes
Square root of the quantity x plus 7 end quantity minus 1 equals x

User RbtLong
by
5.2k points

1 Answer

4 votes

Answer:

x = 2

Explanation:

√(x + 7) − 1 = x

√(x + 7) = x + 1

x + 7 = (x + 1)²

x + 7 = x² + 2x + 1

0 = x² + x − 6

0 = (x + 3) (x − 2)

x = -3 or 2

Check for extraneous solutions:

√(-3 + 7) − 1 = -3

√4 − 1 = -3

2 − 1 = -3

1 = -3

x ≠ -3

√(2 + 7) − 1 = 2

√9 − 1 = 2

3 − 1 = 2

2 = 2

x = 2

User Nathan Noble
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.